Application Of The Simplex Method On Profit Maximization In Baker's Cottage - Nur Zafira Mohd Azman; Nurul Akmal Mohamed; Nurul Farihan Mohamed; Muzirah Musa (Institute of Advanced Engineering and Science (IAES), 2024)
Indexed by Scopus